Lakpesdam dan Gerak Intelektualisme Kaum Muda Nahdlatul Ulama Madura - Fathol Haliq (LPTNU Sumenep, 2023)
Lakpesdam NU Sumenep plays a significant role in coordinating the activities of NU's youth, helping to overcome challenges such as funding shortages, and providing community education. They possess a strong idealism in empowering the community and combine intellectualism with social activism. In their efforts, they face challenges related to relationships with donor organizations and the complexities of power dynamics within society. This study is a field research conducted in the regency of Sumenep. The main research locus is the Institute for the Study and Development of Human Resources (Lakpesdam) of Nahdlatul Ulama (NU). This article presents various empowerment models, such as grassroots, lobbying, and mobilizing, and emphasizes the importance of synergy between civil society organizations, the government, and the private sector in supporting community empowerment. Overall, this article illustrates the vital role of NU's youth in transforming the social and cultural dynamics in Indonesia.